Pengaruh Profitabilitas, Likuiditas, Keputusan Pendanaan, dan Kebijakan Dividen terhadap Nilai Perusahaan - Indah Cholifah; Tumirin Tumirin (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to examine the influence of profitability, liquidity, funding decisions and dividend policy on company value. This type of research is quantitative research. The population in this study are financial and basic materials sector companies listed on the Indonesian Stock Exchange. Then the sample obtained in this research was 211 companies using purposive sampling. The data used in this research is secondary data obtained via the website www.idx.co.id . The analytical method used is descriptive statistical analysis using the SPSS program. The results of this research show that the profitability ratio (ROA) and dividend policy (DPR) have a significant positive effect on company value. Liquidity Ratio (CR) and Funding Decision Ratio (DER) have a significant negative effect on Company Value.